2018
DOI: 10.1038/s41598-018-33866-1
|View full text |Cite
|
Sign up to set email alerts
|

Matured Hop-Derived Bitter Components in Beer Improve Hippocampus-Dependent Memory Through Activation of the Vagus Nerve

Abstract: Improving and maintaining memory function is effective in preventing cognitive decline and dementia. Previously, we demonstrated that iso-α-acids, the hop-derived bitter components in beer, prevent cognitive impairment in an Alzheimer’s disease mouse model. In this report, we investigated the effects of matured hop bitter acids (MHBA) containing components of oxides derived from α- and β-acids, and structurally similar to iso-α-acids, on cognitive function using behavioral pharmacological procedures. MHBA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 51 publications
1
37
0
2
Order By: Relevance
“…This is the first study to show that MHBAs containing β-tricarbonyl moiety improved memory impairment caused by brain inflammation and to indicate the association between the norepinephrine system and vagal nerve activated by MHBAs and memory improvement. Previous studies have shown that MHBAs activate the vagus nerve and increase the levels of noradrenaline, resulting in the improvement of memory impairment 22 . A clinical trial showed that supplements with MHBAs improved cognitive function in older adults with subjective cognitive decline 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to show that MHBAs containing β-tricarbonyl moiety improved memory impairment caused by brain inflammation and to indicate the association between the norepinephrine system and vagal nerve activated by MHBAs and memory improvement. Previous studies have shown that MHBAs activate the vagus nerve and increase the levels of noradrenaline, resulting in the improvement of memory impairment 22 . A clinical trial showed that supplements with MHBAs improved cognitive function in older adults with subjective cognitive decline 26 .…”
Section: Discussionmentioning
confidence: 99%
“…To measure the level of noradrenaline in the brainstem, according to a previous report 22 , the tissue was homogenized in 0.2 M perchloric acid (Wako) containing 100 μM EDTA•2Na (Sigma-Aldrich). After centrifugation, the supernatant was analyzed by high performance liquid chromatography (HPLC) using an EICOMPAK SC-5ODS column and a PREPAK column (Eicom, Kyoto, Japan) with an electrochemical detection (ECD) unit.…”
Section: Assessment Of Microglia Activation In Ad Transgenic Micementioning
confidence: 99%
“…The effects of MHBAs on memory function were first revealed by Ayabe et al [59]. Intragastric treatment with MHBAs (10 mg/kg) enhanced spatial working memory in a scopolamine-induced amnesia mouse model in the Y-maze test and episodic memory in normal mice in the NORT.…”
Section: Mhbas Enhance Cognitive Function Via Activation Of the Vagusmentioning
confidence: 98%
“…12,119,[125][126][127][128][129][130][131] Flavonoides Efeito antioxidante, anti-inflamatório, prevenção modificações intracelulares por bactérias, melhora das funções cognitivas em idosos, alívio dos sintomas da pré-menopausa (ondas de calor), alívio do estresse, prevenção da diabetes, redução do metabolismo de células cancerígenas, inibição da osteoporose e auxilia no combate a úlceras. 48,74,[137][138][139][140][141][142][143][144]122,123,128,[132][133][134][135][136] Fibras Melhora o trânsito intestinal 119…”
Section: Etanolunclassified
“…Ação antifadiga, aumenta a eficácia de tratamentos contra infecções e diabetes, atua no metabolismo dos carboidratos e auxilia no combate a depressão. 133,134,[149][150][151][152] Aminoácidos Reparação muscular, produção de energia e proteínas, melhora na memória, auxilia na resistência física, atua na síntese de colágeno e elastina, envolvidos na resposta imunológica do nosso corpo, podem estar associados a bons níveis de serotonina, contribuindo contra a depressão. 53,128 Carboidratos Principal fonte de energia utilizado pelo nosso corpo.…”
Section: Xanthohumolunclassified